The Context of Recreational Sports for Women in Iran - Elahe Saadatifard; Mohammad Javadipour; Habib Honari; Marjan Saffari; Hossein Zareian (The Society of Aging and Physical Activity (SAPA), 2019)
Background. Given the importance of women and their role in society, women's recreational sports are considered as one of the major issues in the fields of sports and leisure. Objectives. This qualitative study, which was conducted using an exploratory approach, aims to determine the contextual conditions of Iranian women's recreational sports. Methods. The statistical population of the research consisted of all the experts who had practical and scientific expertise in the fields of recreational sports and women's sports is conducted with a method and was selected using Purposive Sampling and Snowball method. Data collection tools included interviews and note-taking processes. After conducting 17 interviews (with 16 elites and 1 Canon group), the researcher reached theoretical saturation and after the data collection procedure, the data was analyzed using MAXQDA10 software and Qualitative Content Analysis. Results. 1254 initial codes or open codes were extracted after the analysis. To further categorize the data, the codes and raw data were constantly compared based on the similarities and differences, and similar codes were placed under the same category. The initial categorization of codes yielded 51 sub-categories which were further categorized into 22 categories in the next step. The obtained concepts were divided into eight major categories (in stage of selective coding) which consisted of socio-cultural, fundamentals of Islam, political, economic, geographical environments and macro-management, media and advertisement, and sports facility issues. Conclusion. Considering the importance of recreational sports in women, a proper understanding of the context of recreational sports can help the sport managers to apply appropriate strategies to develop it and compensate for its backwardness.